“STUDY OF SERUM HIGH SENSITIVE C-REACTIVE PROTEIN IN PREDIABETES” - Ghule, Aishwarya Dilip; Kamble, T.K; Garikapati, Amrutha (International Journal of Psychosocial Rehabilitation, 2020)
Prediabetes is an early stage of hyperglycemia , which progresses to diabetes mellitus , which further increases risk of developing complications. High sensitive C- reactive protein (hsCRP) is an acute phase protein released in inflammation. HsCRP is found in association with diabetes and cardiovascular risk factors.To study high sensitive serum C - reactive protein in prediabetes.The patients who are diagnosed as prediabetes as per the WHO criteria as impaired fasting blood glucose and/or impaired glucose tolerance test by glucose oxidase method will be taken for study. Detail history and examination will be done. BMI, hip circumference, waist circumference, waist hip ratio and blood pressure will be measured for every individual case and control.The results of the study is expected to be an increase in hsCRP levels in the population with prediabetes. Suggest elevated hsCRP levels in cases with prediabetes.